AC susceptibility and hyperfine interactions of vanadium substituted barium nanohexaferrites. Issue 15 (15th October 2018) - Almessiere, M.A.; Slimani, Y.; Güngüneş, H.; El Sayed, H.S.; Baykal, A.
Abstract: Vanadium ions substituted BaFe12 O19 nanohexaferrites, BaFe12-x Vx O19 (0.0 ≤x ≤ 0.1), were produced through the sol-gel auto-combustion route. The structure, morphology and the elemental compositions of various products were examined using X–ray powder diffraction, scanning electron microscopy coupled with EDX and EDS elemental mapping. These techniques confirmed the formation of the desired Ba-nanohexaferrite phases. The crystallites size was found to be 55–58 nm range for all products. The magnetic properties of BaFe12-x Vx O19 nanohexaferrites were investigated by Mossbauer spectroscopy, ZFC-FC magnetizations and AC susceptibility. The evolutions in the values of hyperfine magnetic field, isomer shift, quadrupole splitting, and line width were deduced via Mossbauer analysis. The experiments of ZFC and FC magnetizations indicated that no blocking temperature is observed in the temperature interval 2–400 K, which signals the typical ferromagnetic (FM) behavior for the produced nanohexaferrites. A super-spin glass like behavior is noticed at lower temperatures. The experiments AC susceptibility confirmed that the strength of magnetic interactions is enhanced for lower content of V 3+ (x = 0.02). For higher amount of V 3+, the magnetic interactions are weakened. The obtained results are mainly accredited to the substitutions of Fe 3+ ions by V 3+ ions.